15 The Public Records Of The Colony Of Connecticut, Hartford 191 (Charles J. Hoadly ed., 1890) (enacted 1775) - (:unkn) unknown (My University, 1775)
Prohibited the exportation of salt petre, nitre, or gun powder out of the colony by land or water. Violators fined twenty pounds for every hundred weight of salt petre, nitre, or gun powder.
Keywords: GUNPOWDER - TRANSPORTATION